Facilitation of American Chestnut (Castanea dentata) Seedling Establishment by Pinus virginiana in Mine Restoration. (25th March 2012) - Bauman, Jenise M.; Keiffer, Carolyn H.; Hiremath, Shiv
Abstract : This study evaluated the influence of planting sites on the establishment and ectomycorrhizal (ECM) colonization of American chestnut ( Castanea denetata (Marsh.) Borkh.) on an abandoned coal mine in an Appalachian region of the United States. Root morphotyping and sequencing of the fungal internal transcribed spacer (ITS) region were used to identify the ECM species associated with the chestnut seedlings. Germination, survival, ECM root colonization, and growth were assessed in three habitats: forest edge, center (plots without vegetation), and pine plots (a 10-year-old planting of Pinus virginiana ). Seedlings in pine plots had higher survival (38%) than the other plot types (center 9% and forest edge 5%; P = 0.007 ). Chestnuts found colonized by ECM within the pine plots were larger (P = 0.02 ), contributed by a larger root system (P = 0.03 ). Forest edge and pine plots had more ECM roots than seedlings in center plots (P = 0.04 ). ITS fungal sequences and morphotypes found among chestnut and pine matched Scleroderma, Thelephora, and Pisolithus suggesting these two plant species shared ECM symbionts. Results indicated that the presence of P. virginiana had a greater facilitative effect on growth and survival of chestnut seedlings.